The Knowledge Triangle between Research, Education and Innovation – A Conceptual Discussion - Maximilian Unger; Wolfgang Polt (Foresight and STI Governance, 2017)
This paper discusses the concept of the knowledge triangle (hereafter ‘KT’), as it has gained importance in recent years as a framework for innovation policies especially in OECD countries, especially Europe. The concept has gained popularity because it emphasizes an integrated (‘systemic’) approach on the interlinkages between research, education and innovation. In this article, we highlight the key features of this concept and try to contextualize it with other, at times overlapping, at times complementary, concepts, such as the ‘third mission’, ‘triple helix’ (or in an extended understanding, the ‘quadruple helix’), ‘entrepreneurial or civic university’ models and ‘smart specialization’. Against this background we seek to analyze the roles, rationalities and challenges of different actors that are involved in activities relating to each of the three spheres of the triangle. Actors are first and foremost higher education institutions (HEIs), public authorities, research and technology institutes and private sector companies.